HD 183579b: a warm sub-Neptune transiting a solar twin detected by TESS. Issue 2 (2nd August 2021) - Gan, Tianjun; Bedell, Megan; Wang, Sharon Xuesong; Foreman-Mackey, Daniel; Meléndez, Jorge; Mao, Shude; Stassun, Keivan G; Howell, Steve B; Ziegler, Carl; Wittenmyer, Robert A; Hellier, Coel; Collins, Karen A; et al.
ABSTRACT: We report the discovery and characterization of a transiting warm sub-Neptune planet around the nearby bright ( V  = 8.75 mag, K  = 7.15 mag) solar twin HD 183579, delivered by the Transiting Exoplanet Survey Satellite ( TESS ). The host star is located 56.8 ± 0.1 pc away with a radius of R *  = 0.97 ± 0.02  R ⊙ and a mass of M *  = 1.03 ± 0.05  M ⊙ . We confirm the planetary nature by combining space and ground-based photometry, spectroscopy, and imaging. We find that HD 183579b (TOI-1055b) has a radius of R p  = 3.53 ± 0.13  R ⊕ on a 17.47 d orbit with a mass of M p  = 11.2 ± 5.4  M ⊕ (3σ mass upper limit of 27.4  M ⊕ ). HD 183579b is the fifth brightest known sub-Neptune planet system in the sky, making it an excellent target for future studies of the interior structure and atmospheric properties. By performing a line-by-line differential analysis using the high-resolution and signal-to-noise ratio HARPS spectra, we find that HD 183579 joins the typical solar twin sample, without a statistically significant refractory element depletion.